2014
DOI: 10.1111/jhn.12205
|View full text |Cite
|
Sign up to set email alerts
|

Poor quality diet is associated with overweight status and obesity in patients with polycystic ovary syndrome

Abstract: Dietary interventions focused on improvement of diet quality should be targeted to treat patients with PCOS because obesity in these women is associated with worsening endocrine, metabolic and reproductive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Homocysteine concentrations were higher as well, although this did not reach statistical significance. The study of Rodrigues et al supports this finding showing a poor diet quality in PCOS patients (56% inadequacy according to the Brazilian healthy eating index) [ 36 ]. Studies comparing diet quality in PCOS to controls are contradictory.…”
Section: Discussionmentioning
confidence: 73%
“…Homocysteine concentrations were higher as well, although this did not reach statistical significance. The study of Rodrigues et al supports this finding showing a poor diet quality in PCOS patients (56% inadequacy according to the Brazilian healthy eating index) [ 36 ]. Studies comparing diet quality in PCOS to controls are contradictory.…”
Section: Discussionmentioning
confidence: 73%
“…Cross-sectional studies have associated low diet quality with obesity 30 , cardiovascular risk factors 31 and systemic inflammation 32 . A meta-analysis of cohort studies concluded that diets with high quality scores were associated with a significant reduction in the risk of all-cause mortality, cardiovascular disease, cancer and type 2 diabetes mellitus 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple environmental and/or genetic factors contribute to the pathogenesis of PCOS (5,7,8) . Lifestyle modifications are considered as the first-line treatment for women with PCOS (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%